Urbanistinė konversija Vilniaus miesto plėtros kontekste pagal bendrojo plano 2015 metams sprendinius - Leitanaitė, Rūta (Journal of Architecture and Urbanism, 2007)
Urban conversion in the context of Vilnius city development according to solutions of master plan for 2015Following the principles of sustainable development, one of the priorities, set in the new Master Plan of Vilnius, is development of a compact city. One of the instruments to achieve it is urban conversion. A convertible territory is a territory, which doesnt correspond to city‘s development priorities, its urban structure, or is injurious to the environment.There are two types of convertible territories defined in Vilnius: the former or is existing industrial zones and territories of collective gardens.Convertible territories are set after analysing them by criteria describing their impact on the city’s urban, environmental, economic, social qualities.When setting the regulations of conversion and future function of a territory, future sustainable connections with the adjacent urban and functional structures are the essential thing.The main principle of urban conversion is the multifunctional use, accentuating the necessity of public, social infrastructure. The regulations for convertible areas are analogous to the ones set for newly developing areas.The main part of the former industrial territories is to be converted into multifunctional (residential, commercial, public) zones, giving priority to the ones located in the city centre or local centres. All the territories of collective gardens are to be converted into single-family housing areas.The process of implementation of the regulation and control of urban conversion isn’t unquestionable. Improvements of the method are suggested referring to the experience of other European cities.Article in Lithuanian.Santrauka. Pateikta Vilniaus BP konvertuojamų teritorijų samprata ir tipai, aptariamas jų potencialo nustatymo būdas. Pristatoma konvertuotinų teritorijų Vilniaus mieste identifikavimo metodika; apžvelgta teikiama Vilniaus miesto savivaldybės teritorijos bendrajame plane iki 2015 metų teritorijų konversijos reglamentų nustatymo metodika bei konversijos reglamentų siūlymai konkrečioms miesto teritorijoms. Aptariami teritorijų konversijos sprendinių įgyvendinimo ir reguliavimo Lietuvoje mechanizmo trūkumai bei Europos miestų patirtis šioje srityje, išskiriant optimalius metodus. Apžvelgiama urbanistinės konversijos reguliavimo problema žemesnio nei bendrasis planas rango teritorijų planavimo dokumentuose.Reikšminiai žodžiai: bendrasis planas, darnioji plėtra, antrinis teritorijų panaudojimas, dykra, urbanistinės konversijos reguliavimas.First published online: 21 May 2013